Physiological and performance responses to 120-minutes of soccer-specific exercise - Harper, L. D.; Watson, A.; West, D. J.; Stevenson, E.; Russell, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The physiological and performance responses to 90-min of soccer-specific activity have been extensively researched. An additional 30-min period of extra-time (ET) is played in specific tournament matches where scores are level at the end of 90-min. There is currently no data profiling the responses observed when ET is played. Therefore, we assessed the physiological and performance response to 120-min of simulated soccer match-play. Methods: Nine university soccer players (age: 20±2 years, VO2max: 54.6±0.9 ml.kg/min) performed a modified version of the Soccer Match Simulation (SMS; Russell et al., 2010) adapted to include ET. During exercise, 15-m sprint velocity, heart rate (HR) and rate of perceived exertion (RPE; Borg, 1982) were measured. Peak lower body power output (PPO) measured using countermovement jumps (CMJ) was assessed before and after each half of normal time (pre-exercise, post 1st half, pre 2nd half, post 2nd half) and post-exercise (post-ET). Results: Sprint velocities reduced by 6.1±4.7% in the last 15-min of ET compared to the same time in the second half (5.2±0.7 m/s vs. 5.5±0.5 m/s, P<0.05), and were significantly reduced compared to all other 15-min blocks (P<0.05). Similarly, decrements of 15-m sprint performance were greater in the final 15-min of ET compared to the last 15-min of normal time (17.2±9.5% vs. 8.6±3.5%, P<0.05). RPE was significantly higher during ET (18±1 units) compared to both the first (15±1 units) and second (16±2 units) halves (both P<0.01), whereas peak and mean HR responses during ET (189±12 beats/min, 166±10 beats/min, respectively) were similar to the first (191±10 beats/min, 169±12 beats/min, respectively) and second (191±12 beats/min, 166±11 beats/min, respectively) halves. PPO was reduced post-ET compared to post 2nd half (3382±321W v 3465±292W, -2.3%, P<0.05). Discussion: This study is the first to investigate the physiological and performance responses to 120-min of soccer-specific exercise. Sprint velocities and PPO were lower in the final stages of ET when compared to the end of normal time. Therefore, it is plausible that soccer-specific fatigue manifests its effects more so during ET, causing further decrement to markers that are crucial to success in soccer. The subjective responses commonly associated with exercise intensity support a greater physiological challenge towards the end of ET. Therefore, the efficacy of interventions that attenuate reductions in performance throughout the ET period remain to be investigated and thus provide future research opportunities.